Indicators for mental well being among undergraduate students in IIUM - Ismail, Abdulfatai Olohunfunmi (Kulliyyah of Education, International Islamic University Malaysia, 2016)
The purpose of this study is to propose mental well being indicators' model for higher institution undergraduate students. Based on this, triangulation mixed method was used, whereby 1200 questionnaire containing the Warwick Edinburg mental well being Scale, Brief Resilience Scale, Personal growth scale, Social Interest Inventory Exercise, Self Acceptance Scale, Personal Goal and Religiosity Scale were distributed to undergraduate students (males and females) at the International Islamic University Malaysia. Then four practicing counsellors from the University Counselling Unit with a lecturer specialized as clinical psychologist from the Kulliyyah of Islamic Revealed Knowledge and Human Science (IRKHS) were interviewed respectively for the qualitative data collection. Principal Component Analysis (PCA) and confirmatory Factor Analysis were conducted to assess the psychometric properties of the scales used. In the same vein, full fledge Structural Equation Modelling was conducted to test the hypothesized model as well as Structural Invariance Analysis was conducted to test the moderating effect of students' gender and sponsorship status. SPSS (version 21.0) and AMOS (Version 21.0) were used in the analysis. The findings from both qualitative and quantitative data revealed that, social interest, resilience, personal goal, personal growth and self acceptance represent strong indicators for mental well being of undergraduates' students of IIUM. The findings equally indicated that, the concept of Taqwa (piety) plays a mediating role between the students' mental well being and the indicators. The major implication of the present study is that, it provides a measurable model for higher institution students to practically assess their mental well being status. The research also contributes to the body of knowledge and existing literature by discovering empirically that, Taqwa (piety) plays mediating role between mental well being and well being indicators of higher institution students.